Macrophage polarization in osteoarthritis progression: a promising therapeutic target - Zhang, Yanlei; Ji, Quanbo (Frontiers in Cell and Developmental Biology, 2023)
Osteoarthritis (OA) is one of the leading causes of pain and disability in the elderly. Synovitis, cartilage destruction and osteophyte formation histologically manifest OA. Unfortunately, there is currently no effective therapy to delay its progression and the underlying mechanisms of OA require further exploration. Macrophage is a main cellular component of joint synovium. It is highly plastic and can be stimulated to polarize to different phenotypes, namely, the pro-inflammatory phenotype (M1) and the anti-inflammatory/tissue-repairing phenotype (M2). Ample evidence has demonstrated the vital roles of macrophages in the progression of OA. Imbalanced M1/M2 ratio is significantly related to OA severity indicating macrophage polarization might be a promising therapeutic target for OA. In this review, we summarized the involvements of polarized macrophages in synovitis, cartilage degradation, osteophyte formation and OA-related chronic pain. Promising therapies targeting macrophage polarization including the intra-articular cell/derivates-based therapy and the alternative non-invasive intervention such as photobiomodulation therapy were reviewed as well.